2019
DOI: 10.1111/bjh.16158
|View full text |Cite
|
Sign up to set email alerts
|

JAK1/2 pathway inhibition suppresses M2 polarization and overcomes resistance of myeloma to lenalidomide by reducing TRIB1, MUC1, CD44, CXCL12, and CXCR4 expression

Abstract: Monocytes polarize into pro-inflammatory macrophage-1 (M1) or alternative macrophage-2 (M2) states with distinct phenotypes and physiological functions. M2 cells promote tumour growth and metastasis whereas M1 macrophages show anti-tumour effects. We found that M2 cells were increased whereas M1 cells were decreased in bone marrow (BM) from multiple myeloma (MM) patients with progressive disease (PD) compared to those in complete remission (CR). Gene expression of Tribbles homolog 1 (TRIB1) protein kinase, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 44 publications
(65 reference statements)
2
71
0
Order By: Relevance
“…38 We have recently reported that one potential mechanism through which RUX may provide anti-MM effects is inhibition of M2 polarisation of macrophages. 18 Interestingly, an increase in PD-L1 in the maternal blood initiates PD-L1/PD-1-mediated polarisation of macrophages toward M2 and leads to immune tolerance during gestation. 39 We have found another novel way to regulate the PD-L1/ PD-1 pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 We have recently reported that one potential mechanism through which RUX may provide anti-MM effects is inhibition of M2 polarisation of macrophages. 18 Interestingly, an increase in PD-L1 in the maternal blood initiates PD-L1/PD-1-mediated polarisation of macrophages toward M2 and leads to immune tolerance during gestation. 39 We have found another novel way to regulate the PD-L1/ PD-1 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Reverse transcription polymerase chain reaction (RT-PCR) and quantitative analysis were performed as previously described. 18 Total RNA was extracted using the RNeasy kit (Qiagen, Louisville, KY, USA). The complementary DNA (cDNA) was synthesised using a Superscript III reverse transcriptase kit (Life Technology, Grand Island, NY, USA).…”
Section: Reverse Transcription Polymerase Chain Reaction (Rt-pcr) Andmentioning
confidence: 99%
“…Total RNA were extracted from cells with Nucleospin RNA extraction Kit (Macherey-Nagel) and reverse transcribed using the High-Capacity cDNA Reverse Transcription Kit (Applied Biosystems, Thermo Fisher Scientific). qPCR assays were next performed using the fluorescent dye SYBR Green methodology and a CFX384 Real-Time PCR detector (Bio-Rad Laboratories, Marnes-la-Coquette, France), as previously described (18). The KiCqStart® SYBR® Green primers for human and mouse cDNA were provided by Sigma-Aldrich.…”
Section: Reverse Transcription-quantitative Polymerase Chain Reactionmentioning
confidence: 99%
“…A systematic phenotypic and functional evaluation of the impact of different JAK inhibitors on the broad spectrum of activations states of macrophages is therefore mandatory. Moreover, there are conflicting results in the literature concerning in vivo effects of JAK inhibitors, as some studies report a switch from M1 to M2 activation after exposure to JAK3/JAK2 inhibitors such as tofacitinib (17) whereas a decrease of M2 polarization markers has been described after JAK2/1 inhibition by ruxolitinib (18). The precise impact of JAK inhibitors on a wide spectrum of activation states of macrophages is all the more important as the concept of a mutually exclusive M1/M2 polarization profile is more and more controverted, with a constant need of new relevant in vivo models to better approach this issue (19).…”
Section: Introductionmentioning
confidence: 99%
“…27 The same research group showed that ruxolitinib may provide anti-myeloma effects by inhibiting M2 polarisation of macrophages. 28 Importantly, in vitro data suggests that tofacitinib may be better at reversing the bone marrow microenvironmental effects seen in myeloma than ruxolitinib, indicating the importance exploring a range of JAK2 inhibitors in experimental models. 29 Ruxolitinib has been shown to upregulate CD38 expression and increased daratumumab activity in vitro, 30 identifying the need for future combination studies with anti-CD38 monoclonal antibodies such as daratumumab and isatuximab.…”
mentioning
confidence: 99%